Land-Atmosphere Interactions and Effects on the Climate of the Tibetan Plateau and Surrounding Regions - Ma, Yaoming; Jia, Li; Menenti, Massimo; Zhong, Lei (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is focused on recent advances in land-atmosphere interactions and their effects on climate change over the Tibetan Plateau and surrounding regions using multisource remote sensing data and in situ measurements. Retrieval of land surface variables and surface heat fluxes as well as change monitoring in snow, glaciers, lakes, and other land-surface covers are of particular interest. Special attention is given to the retrieval of land-surface key properties, variations in land-surface heat fluxes, estimation of precipitation and evapotranspiration, change monitoring of glacier and lakes, the responses of lakes to climate change, carbon, water and heat exchange in terrestrial ecosystems, risk assessment of snow disasters, estimation of turbulence characteristics, and vegetation dynamics and its response to weather and climate. This reprint was funded by the Second Tibetan Plateau Scientific Expedition and Research Program (Grant No. 2019QZKK0103); National Natural Science Foundation of China (Grant No. 42230610, 91837208, 41875031).